The Comparative Study: Self Acceptance, Environmental Development and Depression on Elderly - Wiliyanarti, Pipit Festy; Rofiatin, Irma; Nasrullah, Dede; Yulianto, Yulianto (Health Notions, 2018)
Depression is a mental health problem that most often experienced by the elderly, but it is often undetectable and poorly handled. Elderly with self-acceptance and lack of environmental mastery is one of the problems affecting the Depression. The research method used comparative study with cross sectional approach. The study population is elderly living in nursing home and living with family in Penjaringan Sari, Surabaya. Sample was 100 elderly, selected using simple random sampling (elderly in nursing home) and cluster sampling (elderly in community). Geriatric Depression Scale (GDS) questionnaire and well-being psychological questionnaires were used. Data were analyzed using Spearman and Mann Whitney test. Based on the result of the test to know the correlation between self-acceptance and depression level in elderly people using Spearman, the correlation coefficient = 0.516 (nursing home) and 0.765 (community), p-value = 0.000 (p <0.05). The coefficient correlation of environmental mastery with depression = 0.658 (at institute and at community 0.755, with p-value = 0.001 (p <0.05), comparative test use Mann Whitney to know difference of self acceptance, environmental control, and level of depression in elderly living in nursing home and community obtained p-value = 0.023 for self-acceptance, environmental mastery p = 0.035 and whereas the depression level difference p = 0.016 in elderly living in the orphanage and living with the family. There was a difference of self-acceptance, environmental mastery with depression level in elderly in nursing home and elderly living with family in society